Flash pulmonary oedema associated with paroxysmal supraventricular tachycardia: report of two cases - Kathleen Seddon; Inmaculada Cerrada Serra; Joonbum Seo (Journal of Feline Medicine and Surgery Open Reports, 2023)
Case summary We describe two cats that had episodic tachypnoea and increased respiratory effort during periods of paroxysmal supraventricular tachycardia (SVT). Thoracic radiographs at the time of clinical signs were consistent with cardiogenic pulmonary oedema. Echocardiography following stabilisation revealed a hypertrophic cardiomyopathy phenotype with normal left atrial size in both cats. The first cat was initially treated with diltiazem, but this did not reduce the frequency of the clinical episodes. Diltiazem was switched to atenolol and the cat remained well without further recurrence. At the time of writing, the cat was reported to be well, 3 years after the initial diagnosis of SVT. The second cat was first managed with diltiazem and was then transitioned to atenolol due to recurrent clinical episodes. The episodes were less frequent with atenolol but still present. Therefore, atenolol was changed to sotalol. The cat remained well on sotalol for 2 years with only one recurrent episode during a painful event. The patient then suffered a sudden cardiac death, 5 years after the initial diagnosis of SVT. Relevance and novel information To our knowledge, this is the first report that describes flash pulmonary oedema developing secondary to episodic paroxysmal SVT in cats. Despite the severity and speed of respiratory compromise, prognosis may be good with an adequate arrhythmia control.